ChemInform Abstract: A Facile Way to Synthesis KMgF3 and Its Luminescent Property with Eu Doping. Issue 31 (11th July 2013) - Wang, Wei; Liu, Xiaoyang; Zhang, Jingchao; Ji, Ying; Jiang, Nan; Ma, Bing; Wang, Xiaofeng; Liu, Li
Abstract KMgF3 and KMgF3:Eu are prepared by molten salt synthesis from mixtures of KCl, MgCl2, Eu(NO3)3, and NH4HF2 as fluorine source and fluxing agent (autoclave, 180 °C, 24 h).